Hemoglobin A1c Level is Associated with Lymphovascular Space Invasion in Diabetic Endometrial Cancer Patients - Ayse Rabia Senkaya; Sercan Kantarci; Suna Yildirim Karaca; Muzaffer Sanci (Gynecology Obstetrics & Reproductive Medicine, 2024)
Objective: Our aim in this study is to examine the relationship of hemoglobin A1c (HbA1c) and fasting glucose with the stage, grade and histological type of cancer and its value in predicting the prognosis of endometrial cancer in diabetic endometrial cancer patients.